Aminocatalytic stereoselective synthesis of (E)-α-naphthyl enals via cross-coupling-like reaction of 1-bromo-2-naphthols with enals - Xixi Song (KeAi Communications Co. Ltd., 2021)
A diphenyl prolinol TMS ether-catalyzed stereoselective reaction of 1-bromo-2-naphthols with enals has been developed. The organocatalyzed cross coupling-like reaction servers an efficient approach to sterically congested (E)-α-naphthyl enals. The formal C(sp2)-C(sp2) cross-coupling products are obtained in good yields and with excellent stereoselectivities in favor of E-isomers. A broad range of aromatic enals and 1-bromo-2-naphthols are tolerated. The synthetic strategy significantly expands the scope of the organocatalytic cross-coupling-like reactions by enabling sterically demanding 1-bromo-2-naphthols as viable substrates.